Development of Student Activity Management Model to Enhance Promote Desired Student Characteristics in Schools Under the Surin Provincial Primary Educational Service Area Office - Kangkan, Wuttichai; Sakpakornkan, Narumon; Prachanant, Nawamin (Ratchaphruek Journal, 2026)
This research aimed to: 1) Develop an administrative model for student development activities to enhance desirable characteristics; and 2) Evaluate the administrative model for student development activities in promoting desirable characteristics. The study was conducted by examining exemplary schools with best practices in student development activity administration through interviews with 3 school directors. The draft model was validated through focus group discussions with 10 experts selected through purposive sampling. The research instruments included interview recording forms, focus group discussion recording forms, and evaluation forms for assessing the accuracy and appropriateness of the model by 5 experts. The feasibility and utility were evaluated by 30 school directors. The instrument used was a 5-point Likert scale evaluation form. Data were analyzed using mean and standard deviation. The research findings revealed that: 1) The administrative model for student development activities to enhance desirable characteristics comprised three dimensions: the administration of guidance activities to enhance desirable characteristics, the administration of student activities to promote desirable characteristics, and the administration of social and public service activities to enhance desirable characteristics. 2) The evaluation results of the administrative model indicated that the accuracy and appropriateness were at the highest level.